Derivation and validation of clinical prediction model of postoperative clinically important hypotension in patients undergoing noncardiac surgery - Yang, Stephen (My University, 2020)
Introduction Postoperative medical complications are often preceded by a period with hypotension. Postoperative hypotension is poorly described in the literature. Data are needed to determine the incidence and risk factors for the development of postoperative clinically important hypotension after noncardiac surgery. Methods The incidence of postoperative clinically important hypotension was examined in a cohort of 40,004 patients enrolled in the VISION (Vascular Events in Noncardiac Surgery Patients Cohort Evaluation) Study. Eligible patients were ≥45 years of age, underwent an in-patient noncardiac surgery procedure, and required a general or regional anesthetic. I undertook a multivariable logistic regression model to determine the predictors for postoperative clinically important hypotension. Model validation was performed using calibration and discrimination. Results Of the 40,004 patients included, 20,442 patients were selected for the derivation cohort, and 19,562 patients were selected for the validation cohort. The incidence of clinically important hypotension in the entire cohort was 12.4% (4,959 patients) [95% confidence interval 12.1-12.8]. Using 41 variables related to baseline characteristics, preoperative hemodynamics, laboratory characteristics, and type of surgery, I developed a model to predict the risk of clinically important postoperative hypotension (bias-corrected C-statistics: 0.73) The prediction model was slightly improved by adding intraoperative variables (bias-corrected C-statistics: 0.75). A simplified prediction model using the following variables: high-risk surgery, preoperative systolic blood pressure <130 mm Hg, preoperative heart rate >100 beats per minute, and open surgery, also predicted clinically important hypotension, albeit with less accuracy (bias-corrected C-statistics 0.68). Conclusion Our clinical prediction model can accurately predict patients’ risk of postoperative clinically important hypotension after noncardiac surgery. This model can help identify which patients should have enhanced monitoring after surgery and patients to include in clinical trials evaluating interventions to prevent postoperative clinically important hypotension.
Keywords: anesthesia; perioperative; Hypotension; noncardiac; prediction model; cohort study